Political paranoia and deception among leaders of some African countries (2006)
In Africa, the need for pragmatic, sincere and purposeful leadership has been discussed at many gatherings, both within and outside the continent. Quite sadly, however, most African nations are still not faring well politically, socially and economically. Poverty, ignorance, fear and intimidation, disease and deprivations of all kinds exist in higher proportions than years gone past. It is no longer news that most of Africa’s problems stem from the continent’s leaders who have found nothing wrong with squandering the wealth of their nations, sometimes, in collaboration with their western partners in corruption. In their characteristic bad governance and indulgence in official corruption, African leaders create for themselves real and imaginary enemies whom they use public funds and other machinery of government to fight. As a way of justifying their acts also, not a few African leaders indulge in acts of deception that are face saving in nature. While employing different means to perpetuate themselves in office, many of the leaders today stop at nothing to see their dreams come true. Known and designated as psychopathology, paranoia in political context refers to pervasive distrust and suspiciousness of others such that their motives are interpreted as malevolent. An important aspect of political paranoia is a pattern of disowning uncomfortable personal feelings and attributing them to others, the psychological defence mechanism known as projection. Political deception, on the other hard, refers to an inducement of false beliefs by political leaders in their followers or the people they lead. This is principally done using propaganda and sometimes intimidation among other methods. Deception includes forgery, imposture, conjuring, military, civil and strategic deceptions and much more. This paper used Nigeria as a case study because the Nigerian socioeconomic and political environment captures the African experience in not a few ways. The paper utilizes a psychological perspective to critically examine the emergence, use, trend and consequences of political paranoia and deception as weapons by the present political leadership in Nigeria where the citizenry appears to be generally not satisfied with the performance of the entire present administration. The aim is to understand the multi-faceted thought and behavioural patterns of African leaders, which are necessary for any meaningful mass political mobilization of the citizenry.